Analisis Akuntabilitas dan Transparansi dalam Kinerja Keuangan Pemerintah Desa : (Studi Fenomologi di Desa Anakalang Kabupaten Sumba Tengah) - Nelson Umbu Maraba Uma (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
This research aims to assess financial performance in managing the 2023 APBDes in Anakalang Village, Katikutana District, Central Sumba Regency. This type of research uses a qualitative approach method, while the data sources used in this research are primary data and secondary data. Primary data was obtained through interviews with several village officials, namely the village head, village secretary, village treasurer and community leaders from the Anakalang tribe. Meanwhile, secondary data was obtained from Village Government data and documents and documentation carried out by researchers at the research location. The data collection technique used in this research is by conducting direct interviews with informants. The informants in this research consisted of the Village Head, Village Secretary, Village Treasurer and Community Figures in Anakalang Village. The results of this research show that financial performance in the management of the APBDes in Anakalang Village is based on the principles of accountability and transparency. Even though it is not in accordance with applicable policies by adjusting the situation or conditions of applicable legislation.